Flame Retardant Coatings: Additives, Binders, and Fillers - Mohd Sabee M.M.S.; Itam Z.; Beddu S.; Zahari N.M.; Mohd Kamal N.L.; Mohamad D.; Zulkepli N.A.; Shafiq M.D.; Abdul Hamid Z.A. (MDPI, 2023)
Binders; Coatings; Fillers; Flame retardants; Flammability; Coating additives; Coating system; Flame retardant coatings; High standards; Intumescence; Intumescent flame-retardant coating; Polymer substrate; Property; Standard of living; Thermal degradation'; Additives